UTILIZATION OF CEPHALOMETRIC 2D AND 3D ANALYSIS DURING DIAGNOSIS, TREATMENT PLAN AND CASE MONITORING OF IMPACTED TEETH-CASE REPORT - Srbinoska, Daniela; Trpevska, Vesna; Cadikovska, Elizabeta (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
RTG projections are essential for diagnosis, treatment plan, follow up and treatment outcomes. Three-dimensional(3D) cephalometry, which is done using a cone beam computerized tomography (CBCT) exam, allows more detailed evaluation of the craniofacial hard and soft tissue structure than 2D radiograph. The justification for using 3D analyses in diagnostic and treatment planning in orthodontics are more than necessary in cases with impacted teeth, cleft lip, skeletal discrepancies requiring surgical interventions. CBCT has come into wider usage in other situations as root resorption, temporomandibular joint (TMJ) morphology and pathology, supernumerary teeth, alveolar boundary conditions and asymmetries; maxillary transverse dimensions and maxillary expansion; vertical malocclusion and obstructive sleep apnoea. The present descriptive study aims to explore possible applications of 3D technologies during the diagnosis, treatment plan, case monitoring and result assessment in orthodontics including their advantages and disadvantages. Utilisation of 3D technique was more than necessary in diagnostic and treatment planning in this case because of presence of more than one impacted tooth. The fixed appliances, the surgical exposure, cortectomy and orthodontic traction were done.  The tooth movement and positioning to the dental arch started six months ago. The impacted tooth is already seen and the treatment continues. The severity of this case is indication for utilization of control 2D and 3D radiographs in manner following the positioning of the central incisor on the appropriate place. 3D technique is less prone to error and can improve the cliniciansâ€™ workflow. Keywords : Diagnosis, Treatment plan, 2D radiograph, CBCT, Cortectomy.